Strategi Dalam Meningkatkan Kompetensi dan Profesionalisme Pustakawan dalam Mengoptimalkan Kembali Reference Service terhadap Pemustaka di Perpustakaan Universitas Negeri Padang - Sumitra, Falian (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2020)
ABSTRACT The reference service at the library is currently less than optimal. Therefore, several strategies are needed to improve the competence and professionalism of librarians in reference services. One of the reference services that still needs optimization in improving the competence of librarians is the Padang State University Library. The method used in this article is a qualitative method with a descriptive approach. This type of research in writing this article uses the Research Library method which means a literature or literature study. The purpose of this research is to find out the strategies used by libraries to improve the competence and professionalism of librarians in reference services and to find out what the obstacles are in the Padang State University Library.